Kurdish EFL Student Teachers’ Perceptions Towards Their School-Based Teaching Practice Course - Mohammad, Zaki H.; B. Al-Azzawi, Mohamed (Humanities Journal of University of Zakho, 2024)
ABSTRACT: Teaching practice holds paramount significance within the domain of teacher education and training, providing student teachers with a tangible opportunity to acquire practical knowledge and firsthand experience in the dynamics of schooling and classroom pedagogy. This study set out to investigate the perceptions of EFL student teachers regarding the school-based teaching practice course in four colleges of education and basic education in Duhok province of the Kurdistan Region-Iraq. A combined qualitative and quantitative methodological approach was used to gather the research data. A paper and online questionnaire provided quantitative data from 132 participants, complemented by conducting semi-structured interviews with 16 student teachers. The results showed that the teaching practice experience was deemed ineffective and inadequate in preparing to become qualified EFL teachers. The results further revealed that the majority of the elements involved in the topic being studied were deemed unsatisfactory and there were multiple areas for improvement in the phenomenon. The implications of these findings extend our understanding of the process and procedures of the teaching practice course in this specific context. The findings presented add to our understanding of the various aspects of the subject. The research has the potential to inform policy decisions and practical interventions, thereby positively influencing the field and leading to tangible improvements. This study holds significant importance as it addresses a critical gap in existing research, shedding light on an area that has thus far been underexplored. A significant limitation of the current study is its exclusive focus on student teachers as the primary data collection subjects. Therefore, future research should consider investigating the perspectives of other stakeholders involved in the teaching practice, including university supervisors, school principals, representatives of English departments, the course developers, and focal persons.